Evolution of the trophy position along the tennis serve player`s development - Tubez, F.; Schwartz, C.; Croisier, J. L.; Brüls, O.; Denoël, V.; Paulus, J.; Forthomme, B. (Sports Biomechanics, 2021)
The trophy position is a coaching cue for the tennis serve that usually corresponds to the racquet high point (RHP) during the preparatory action for the stroke. Mastering this position and its time of occurrence seems essential in overarm movements like in the tennis serve. Clinicians and coaches have a real interest in understanding the trophy position and its evolution during the development of the elite players at different ages. A 3D motion system was used to measure the kinematics of the serve. A group of high-level tennis players were selected for three different age groups: 8 adults (ITN 1), 8 teenagers (ITN 3) and 8 children (ITN 5-6). Results show a modified pattern sequence of the tennis serve between children and adult players. RHP appears earlier relative to impact for children (-0.54 ± 0.10 s) than for adults (-0.36 ± 0.11 s) and teenagers (-0.33 ± 0.05 s) (p = 0.007). At RHP, children present lower trunk transverse plane rotation (p < 0.003) and higher shoulder external rotation (p < 0.003). These positions for the child players may represent an increased risk of shoulder and trunk injury than for older players and contribute to a lower racquet resultant velocity at impact.